The determination of some biochemical contents of Helichrysum armenium DC. subsp. araxinum (Kirp.) Takht - Bahsi, Muammer; Emre, Mustafa Yunus; Emre, Irfan; Kurşat, Murat; Ökkeş,; Yılmaz, Okkes; Yilmaz, (My University, 2020)
ActThe aim of current study was to determine fatty acid compositions, lipid soluble vitamins, phenolic compounds,radical scavenging activities, antioxidant activity and metal chelating capacity of Helichrysum armenium subsp. araxinumextracts. It was found that palmitic acid (C16:0) was primary fatty acid (58,99±1,21%). Current study demonstrated thatlipid soluble vitamin contents were lowest. However, stigmasterol and ?-sitosterol were found as 79,4±1,17 and29,2±0,87, respectively in this study. Also, present study showed that H. armenium subsp. araxinum has highest naringincontent (1156,8±3,57 µg/g) whilst it has high vanillic acid (213,2±2,32 µg/g), caffeic acid (151,6±1,27 µg/g) and ferulicacid (117,94±1,26 µg/g) contents. On the other hand, it was demonstrated that H. armenium subsp. araxinum has highestDPPH (except for 10 µl), ABTS radical scavenging activities and metal chelating capacity in 100 µl.
Keywords: Biyoloji; Kimya; Organik; Kimya; Tıbbi